Effects of Repetitive Transcranial Magnetic Stimulation on Cerebellar Metabolism in Patients With Spinocerebellar Ataxia Type 3 - Chen, Xin-Yuan; Lian, Yan-Hua; Liu, Xia-Hua; Sikandar, Arif; Li, Meng-Cheng; Xu, Hao-Ling; Hu, Jian-Ping; Chen, Qun-Lin; Gan, Shi-Rui (Frontiers in Aging Neuroscience, 2022)
Background: Spinocerebellar ataxia type 3 (SCA3) is the most common autosomal dominant hereditary ataxia, but, thus far, effective treatment remains low. rTMS can improve the symptoms of spinal cerebellar ataxia, but the mechanism is unclear; in addition, whether any improvement in symptoms is related to cerebellar metabolism has not yet been investigated. Therefore, the purpose of this study was to investigate the effects of low-frequency rTMS on local cerebellar metabolism in patients with SCA3 and the relationship between the improvement in symptoms and cerebellar metabolism. Methods: A double-blind, prospective, randomized, sham-controlled trial was carried out among 18 SCA3 patients. Participants were randomly assigned to real stimulation group or sham stimulation group. Each participant in both groups underwent 1 Hz rTMS stimulation, differing only in terms of stimulator placement, for 15 consecutive days. To separately compare pre- and post-stimulation data (MRS data and ICARS score) in the real and sham groups, paired-sample t-tests and Wilcoxon signed-rank tests were used in the analyses. Differences in ICARS and MRS data between the two groups were analyzed with independent t-tests and covariance. To explore the association between changes in concentration of cerebellar metabolism and ICARS, we applied pearson correlation analysis. Results: After treatment, the ICARS scores significantly decreased in the both groups, while the decrease was more significant in the real stimulation group compared to the sham stimulation group (P < 0.001). The values of NAA / Cr and Cho / Cr in the five brain regions increased significantly in the real stimulation group (P < 0.05), but no significant differences were found in the sham stimulation group (P > 0.05). This study also demonstrated that there was a negatively correlation between NAA / Cr in the right cerebellar hemisphere and ICARS in the real stimulation group (r = - 0.831, P = 0.02). Conclusions: The treatment with rTMS over the cerebellum was found to induce changes in the cerebellar local metabolism and microenvironment in SCA3 patients. The alterations may contribute to the improvement of the symptoms of ataxia in SCA3 patients.